Determinan Tingkat Partisipasi Zakat Di Masa Pandemi Covid-19 - Nasution, Hamni Fadlillah; Matondang, Zulaika; Napitupulu, Rodame Monitorir (Journal of Islamic Social Finance Management, 2020)
AbstractEconomic downturn during the pandemic era has caused the poverty rate to increase. One of manners to overcome poverty in Islamic gospel is to give zakah or tithe. The lecturers and employees at IAIN Padangsidimpuan who have permanent stages can become muzakki to help mustahiq get out of their economic downturn. This study aims to analyze the level of zakah participation of lecturers and staff of IAIN Padangsidimpuan during the COVID-19 pandemic. The method used in this research is regression analysis in quantitative research design with primary data. The results showed that the faith and self-satisfaction factors can affect the level of zakah participation, while the appreciation, altruism and organization factor do not affect the level of zakah participation. Keywords: Zakah, Participation, COVID-19